(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2016)
the bank sect for any country is very important because its represent a major nerve to feed a verity economic and finance activities .development any state measure by development banking sets and its represent important factor to investors attract . and because important of this subject ,teen accounting rule is a specialized for it .its related by Disclosures in the Financial Statements Of Banks and The Similar Institutions, its accredit by auditing and accounting standard consul in republic of Iraq.in date 10/28/1998. This rule not adjusted since that time to contain the development and a variables it witnessed this sect for example Islamic and electronic banking Activities witch is speared in Iraq. So that suggested this research some a necessary adjustment for this rule to become more effective Accounting disclosure enhancement in the banking Activities